Advances in Low Carbon Technologies and Transition - Kagawa, Shigemi (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
A wide variety of technologies and products have already become widespread in our society. However, policies have not been well-implemented to effectively reduce energy consumptions and CO2 emissions by promoting low-carbon technologies and products. This Special Issue focuses on studies targeting specific products (e.g., motor vehicle, household dishwashers, etc.) and/or technologies (e.g., information and communication technology, transport technology, CO2 capture technology, etc.) and quantifying resource and energy consumptions and CO2 emissions associated with products and technology systems using the reliable inventory database. Thus, this Special Issue provides important studies on how demand- and supply-side policies can contribute to reducing energy consumptions and CO2 emissions from consumption- and production-based perspectives.